2022
DOI: 10.3390/plants11172242
|View full text |Cite
|
Sign up to set email alerts
|

Achievements, Developments and Future Challenges in the Field of Bioherbicides for Weed Control: A Global Review

Abstract: The intrusion of weeds into fertile areas has resulted in significant global economic and environmental impacts on agricultural production systems and native ecosystems, hence without ongoing and repeated management actions, the maintenance or restoration of these systems will become increasingly challenging. The establishment of herbicide resistance in many species and unwanted pollution caused by synthetic herbicides has ushered in the need for alternative, eco-friendly sustainable management strategies, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 111 publications
0
53
0
Order By: Relevance
“…Among these species, only Collego (LockDown), BioMal, Velgo, and Lubao1 have been successfully commercialized. This genus of fungi has been reported to control various weeds around the world and has excellent potential to develop into a commercial mycoherbicide [ 54 ]. Here, in this study, we demonstrated that C. echinochloae had the potential to be developed as a mycoherbicide for the management of barnyardgrass ( Echinochloa crus-galli (L.) Beauv.).…”
Section: Discussionmentioning
confidence: 99%
“…Among these species, only Collego (LockDown), BioMal, Velgo, and Lubao1 have been successfully commercialized. This genus of fungi has been reported to control various weeds around the world and has excellent potential to develop into a commercial mycoherbicide [ 54 ]. Here, in this study, we demonstrated that C. echinochloae had the potential to be developed as a mycoherbicide for the management of barnyardgrass ( Echinochloa crus-galli (L.) Beauv.).…”
Section: Discussionmentioning
confidence: 99%
“…Even when all of these issues are resolved, it is possible that synthesis of these compounds on sufficiently large scale for field application is prohibitively, or at least antagonistically, expensive (Roberts et al, 2022), owing to their structural complexity and often a lack of preceding work undertaken to optimize their production. Such high production costs of bioherbicides can be an even greater issue if new, cheap, effective ‘traditional’ herbicides are released into the same market; bioherbicidal formulations of the fungus Colletotrichum gloeosporioides f.sp.…”
Section: Applying Allelopathy: Implementation In Weed Managementmentioning
confidence: 99%
“…application is prohibitively, or at least antagonistically, expensive (Roberts et al, 2022), owing to their structural complexity and often a lack of preceding work undertaken to optimize their production.…”
Section: Allelopathy-inspired Bioherbicides and Modes Of Actionmentioning
confidence: 99%
“…103 In addition, recent studies have sought to understand the herbicidal action of different molecules produced by plants, bacteria, fungi, and viruses to generate new modes of action in the commercial scenario to solve cases of resistance. 104 This advantage is related to the multisite action of allelochemicals, an alternative to commercial formulations with high plant specificity. 105 Increasing risk awareness of chemical herbicide use and the imminent ban on glyphosate herbicides in the European Union should further encourage and enable the development of natural alternatives.…”
Section: ■ Microbial-based Herbicidesmentioning
confidence: 99%
“…For example, registration with the Environmental Protection Agency is expensive and can extend the deadlines for bioherbicides to be available for use by farmers. 104 In addition, many countries make no legislative distinction between natural and conventional formulations, restricting the widespread use of all herbicides, including bioherbicides. 132 Bioherbicides remain new to the market, and formulation changes could be necessary to increase efficiency, even after product registration.…”
Section: ■ Microbial-based Herbicidesmentioning
confidence: 99%